Analisis faktor – faktor yang mempengaruhi produksi pada industri rumah tangga (studi kasus : industri kerupuk udang di Desa Lambur Luar Kecamatan Muara Sabak Timur Kabupaten Tanjung Jabung Timur) - Trisa Mushandry Pratiwi; Hardiani Hardiani; Adi Bhakti (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The purpose of this study is (1) To analyze the socioeconomic characteristics of Producers in the Shrimp Crackers Home Industry in the Village of Lambur Luar Tanjung Jabung Timur Regency, (2) To analyze the effect of capital, labor, prices and raw materials on production in the Home Industry Shrimp Crackers in Lambur Luar Village, Tanjung Jabung Timur Regency. The results showed that all independent variables (capital, labor, prices and raw materials) affected the production of the shrimp cracker industry in Lambur Luar Village. Judging from the test results obtained by the coefficient of determination ( ) of 0.963460. This is aimed at capital, labor, prices and raw materials able to influence production by 96.34 percent and the remaining 3.66 percent for other variables not included in this study. Whereas if tested partially, capital, labor, price and raw material variables have a positive and significant effect on production in the shrimp cracker industry in Lambur Luar Village.